2020
DOI: 10.3390/molecules25061284
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characteristics and Anticancer Activity of Essential Oil from Arnica Montana L. Rhizomes and Roots

Abstract: Arnica montana L. is a medicinal plant with diverse biological activities commonly used in pharmacy and cosmetics. The attributes of A. montana are mainly related to the concentration and chemical composition of essential oils (EOs). Therefore, the objective of this study was to characterize the chemical composition of EOs derived from A. montana rhizomes and roots taking into account the age of the plants and to investigate the effect of the analyzed EOs on induction of apoptosis, necrosis, and autophagy in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 73 publications
1
22
0
Order By: Relevance
“…Therefore, they are of interest for scientists worldwide [ 43 ]. It has been shown that numerous EOs demonstrate antimicrobial, antiviral or anticancer activity [ 44 , 45 , 46 , 47 ]. Chouhan at al.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they are of interest for scientists worldwide [ 43 ]. It has been shown that numerous EOs demonstrate antimicrobial, antiviral or anticancer activity [ 44 , 45 , 46 , 47 ]. Chouhan at al.…”
Section: Discussionmentioning
confidence: 99%
“…The inflorescences of the meadow arnica (Arnicae anthodium) have a similar chemical composition and pharmacological activity to that in the mountain arnica (Arnica montana L.) [9,[25][26][27][28]. There are literature reports on the antioxidant, antiseptic, and anti-inflammatory effects [9,14,[29][30][31][32], and the potential use of arnica raw material in Alzheimer's disease and cancer treatment [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, essential oils were tested in melanoma cell lines to assess anticancer activity. Unlike the essential oil from C. abrotanoides [ 14 ] and essential oils from A. montana [ 38 , 39 ], that demonstrated selective cytotoxicity against the cancer cells, C. cernuum REO and APEO did not show selective cytotoxicity towards the cancer cell lines used in this study. Cytotoxic activity of thymol was slightly higher than those of the tested C. cernuum oils.…”
Section: Discussionmentioning
confidence: 75%
“…Recently, thymohydroquinone dimethyl ether from A. triplinervis has been proven to be active against Zika virus in non-cytotoxic doses [ 36 ]. Rhizomes and roots as well as achenes of a popular European medicinal plant Arnica montana L. (tribe Madieae of the Compositae) produced essential oils with a high content of thymohydroquinone dimethyl ether (20–60%), accompanied by smaller amounts of thymol methyl ether (4–27%), that induced apoptosis in cancer cells in vitro [ 37 , 38 , 39 ]. Roots of Cyathocline purpurea (D. Don) O. Ktze (Compositae), a rare Indian medicinal plant, contained essential oil with 2,5-dimethoxy- p -cymene as a major constituent (57%).…”
Section: Discussionmentioning
confidence: 99%